Representations of the social pattern: the pattern of the other reality in the Umayyad poetry - Hason, Makki; Mohammed, Saja (Al-Adab Journal, 2024)
Systematic performance is considered one of the important and advanced methods in Arabic poetry, since ancient times. And the image of the other often mixes the real with the ideal, or the truth with the imaginary, so that it becomes blurred, “just as our vision of the truth about ourselves – with the outside – what we want to show to others is intertwined in its internal information.